2010
DOI: 10.1063/1.3457139
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on ion acceleration and stream line detachment in a diverging magnetic field

Abstract: The flow structure of ions in a diverging magnetic field has been experimentally studied in an electron cyclotron resonance plasma. The flow velocity field of ions has been measured with directional Langmuir probes calibrated with the laser induced fluorescence spectroscopy. For low ion-temperature plasmas, it is concluded that the ion acceleration due to the axial electric field is important compared with that of gas dynamic effect. It has also been found that the detachment of ion stream line from the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…The phenomenon takes place in a globally current free jet, even if electrons remain fully magnetized and turn around with the field; only a negligible fraction of the ion flow is indeed pulled along with the electrons to maintain quasi-neutrality in the whole domain. This result is in agreement with the experimental observations [22]- [24], [26] of ion flux tube separation.…”
Section: Introductionsupporting
confidence: 93%
“…The phenomenon takes place in a globally current free jet, even if electrons remain fully magnetized and turn around with the field; only a negligible fraction of the ion flow is indeed pulled along with the electrons to maintain quasi-neutrality in the whole domain. This result is in agreement with the experimental observations [22]- [24], [26] of ion flux tube separation.…”
Section: Introductionsupporting
confidence: 93%
“…Cox et al 17 and Deline et al 18 observed that the half-width at halfmaximum of the radial density profile diverges less than the magnetic field, from which they conclude that ions have begun to detach from the MN. A similar conclusion was reached by Terasaka et al 19 using Mach probes to spatially map the three-dimensional ion velocity vector. Direct measurements of ion detachment were made using Faraday probe sweeps by Olsen et al 20 In contrast to the previous studies, Olsen et al observe that the ion streamlines of an ED-MN detach outward with respect to the diverging magnetic field.…”
Section: Introductionsupporting
confidence: 56%
“…Inwards ion separation has been observed in several recent experiments. [22][23][24][25] Outwards ion separation, which requires outwards electron separation, has been observed too. 25 The outwards separation of electron streamtubes implies that a stronger radial electric field is needed to pull ions towards the more divergent beam edge and satisfy quasineutrality there.…”
Section: A Plasma Expansion Featuresmentioning
confidence: 99%